God is Watching You : How the Fear of God Makes us Human - Johnson, Dominic (New York Oxford University Press, 2016)
Drawing on new research from anthropology, evolutionary biology, experimental psychology, and neuroscience, Dominic Johnson presents a new theory of supernatural punishment that offers fresh insight on the origins and evolution of not only religion, but human cooperation and society.
Include Index
Keywords: Punishment--Religious aspects -- Religion--Philosophy -- Fear of God